ASUHAN KEPERAWATAN PADA NY.O DENGAN STROKE NON HEMORAGIK DI WILAYAH KECAMATAN LIMO KOTA DEPOK - Charla Bernadhetta Angeline Diovanessa (2023)
Introduction Stroke has the meaning of a condition that is used to explain a neurological change that occurs due to blood circulation to the brain being obstructed or impaired, non-hemorrhagic stroke is a type of stroke caused by blockage in the brain blood vessels either half or all. The purpose of this study is so that the author can have a real picture of the implementation of nursing care in patients with non-hemorrhagic stroke. The research method used in this research is the case study research method. The results of the research obtained were the discovery of nursing problems of impaired physical mobility, risk of falling, and ineffective health maintenance with the main nursing action taken was mobilization support (ROM). The conclusion obtained in the discussion of mobilization support is that there is an increase in muscle strength on day 4 of the nursing visit. The suggestion in this study is that clients should continue to pay attention to health, by maintaining a healthy lifestyle, diligently training muscle strength with independent ROM, diligently checking their health conditions.